Roles of External Carotid Artery Ligation in Neurosurgical Practices: a Literature Review and Suggestion - ไชยบุตร ประดิษฐ์ (Journal of Health Science of Thailand, 2023)
External carotid artery is a major blood supply of head and neck structures including cerebral meninges. With existence of multiple anastomoses between external and internal carotid arteries, ligation of external carotid artery has no disabling complications. Ligation of external carotid artery for control hemorrhage in the area of head and neck is necessary in some conditions. Less invasive arterial embolization has been introduced to an effective alternative. This study aimed to explore the roles of external carotid artery ligation (ECAL) in clinical practices up to the present day, especially in the field of neurosurgery in Thailand which neurovascular interventionists are very few. A medical journal search using MEDLINE and Academic Search Ultimate database and a manual search for the related journals were performed. Inclusion criteria was ECAL that was only used to control bleeding. A total of 766 articles were collected from 1872 to 2021. After removal of the duplications and the unrelated, 192 articles which ECAL was used for controlling hemorrhage were included in the review. The most frequent articles (121 papers) were in orofacial and neck diseases, followed by epistaxis (36 papers), craniofacial trauma (18 papers), brain and skull base lesions (13 papers) and mixed pathology (4 papers). External carotid artery ligation (ECAL) had its roles for neurosurgeons to treat patients with severe hemorrhage from craniofacial trauma and to decrease intraoperative blood loss in vascularized skull-base lesion surgery. Although endovascular interventions are less invasive, but in the setting that lack of intervention facilities or in unstable patients, ECAL is still a life-saving and useful procedure especially for neurosurgical training and practices in Thailand.